No ocaso do império, um projeto de nação : Silvio Romero e a história da literatura brasileira - Lemos, Wagner Gonzaga (2012)
This study is the result of a bibliographic and with study of documents research which deals with the importance of sergipano critic Silvio Romero (1851-1914) and his masterpiece História da Literatura Brasileira (1888) at the end of the nineteenth century. That work is found to be a project of nation, in the different meanings that the word project have, which Romero sought to consolidate through the letters by establishing canons and including in his broad concept of literature a large variety of cultural productions that could be seen at the time. Therefore, his masterwork was the first to conjoin scientific and conceptual principles in Brazilian literary history. In this text, we consider the construction of the national identity in the modern states as well as we deal with nation s narrative relevance from literature s perspective. Moreover, taking into consideration the contextualization of the nineteenth century in Brazil, it was our focus not only Romero s masterpiece, but also European and national authors who analysed literature in our country before him, such as Barbosa Machado, Ferdinand Denis, Gonçalves de Magalhães, Joaquim Norberto Sousa e Silva, Cônego Fernandes Pinheiro and Machado de Assis. In this sense, we discuss the role performed by school in the process of canon legitimation as well as in the affirmation of national letters, considering to this end the importance of literary history compendia, discourses and anthologies. At last, we outline Silvio Romero s biobibliography, including his origins, his intellectual formation, the most famous polemic, his divergent position in his intellectual production context, and we dared to bring to light new aspects related to the aforementioned author. Likewise, we intend to identify aspects in História da Literatura Brasileira in relation to elements which, according to Stuart Hall (2006) and Eric Hobsbawm (2002; 2012), establish a nation s image construct.